Employment Status Analysis of Students in Vocational Colleges under the Background of Industry 5.0 - Yan, Li; Leong, Wai Yie (INTI International University, 2024)
This study analyzes students' employment status in vocational colleges based on Industry 5.0 context. We identify key factors affecting employment rates, and proposes strategies to address the students’ employment potential. The study integrates theory and practice in teaching, optimizing content and methods to meet industry needs, and enhancing students’ employability. The study recommends educational and teaching reforms, including the "dual-teacher" model, entrepreneurship education, industry training, and certification, to improve students' adaptability and competitiveness in the job market. This offers practical guidance for educational institutions and enterprises to enhance the quality of vocational education and meet the talent requirements of modern manufacturing industries.